A new species of Szelenyiopria Fabritius (Hymenoptera: Diapriidae), larval parasitoid of Acromyrmex subterraneus subterraneus (Forel) (Hymenoptera: Formicidae) from Brazil - Loiácono, Marta; Margaría, Cecilia; Moreira, Denise D.o. (Zootaxa, 2013)
Szelenyiopria talitae sp. nov. is described and illustrated. This species is shown to be a larval parasitoid of Acromyrmex subterraneus subterraneus (Forel).